Positional analysis of body composition using dual-energy x-ray absorptiometry in national collegiate athletic association division i football and men's lacrosse - Zabriskie, H. A.; Dobrosielski, D. A.; Leppert, K. M.; Droege, A. J.; Knuth, N. D.; Lisman, P. J. (The Journal of Strength and Conditioning Research, 2022)
Despite the widespread use of dual-energy X-ray absorptiometry (DXA), few studies have examined differences in body composition between positions within sports and none have reported DXA-derived body composition reference values for men's lacrosse. The purpose of this study was to examine differences in measures of total and regional body composition and bone mineral density (BMD) using DXA across sport positions in a large cohort of National Collegiate Athletic Association Division I male lacrosse and football players. A total of 294 male athletes (football, n = 196; lacrosse, n = 98) underwent DXA. One-way analysis of variance or Kruskal-Wallis tests were used to examine whether body composition variables differed by sports position. In football, position was a significant determinant for every compositional variable in football athletes (all, p < 0.05; effect size range = 0.24-0.79). Offensive linemen had the highest total body fat percentage (30.1 ± 2.9%), followed by fullbacks (26.7 ± 3.3%) and defensive linemen (24.6 ± 5.7%); wide receivers had the lowest (14.5 ± 2.1%). For total body BMD, defensive linemen had the highest (1.70 ± 0.09 g·cm-3), followed by linebackers (1.67 ± 0.09 g·cm-3) and offensive linemen (1.65 ± 0.09 g·cm-3); kickers had the lowest (1.45 ± 0.11 g·cm-3) BMD. In lacrosse, no differences were found between positions for any total or regional body composition and BMD measure (all, p > 0.05). Our data confirm that total and regional measures of body composition and BMD vary across positions in football but not in men's lacrosse. Unlike football, similarities in body composition among lacrosse players may indicate that the uniformity of training demands or preferred player attributes in team selection outweigh the unique positional demands in gameplay.